Gambaran Kadar Kolesterol Total Berdasarkan Karakteristik Perokok Pada Perokok Aktif Usia Remaja Di Kecamatan Cilawu Kabupaten Garut - Astari Nurisani; Mamay Mamay; Sugiah Sugiah; Manzilah Ziyan; Engkus Kusnadi (Student Scientific Creativity Journal, 2023)
Smoking is an activity that we are now familiar with. Smoking habits have been proven to cause diseases that attack various organs of the human body. Adolescents as part of society who are at a productive age. Cigarette addiction among teenagers is a severe problem in many countries, including Indonesia. Smoking is one of the factors that increase cholesterol levels in the blood. Nicotine can increase fatty acids that affect total cholesterol levels. The purpose of this study was to describe the total cholesterol levels in active smokers in the light, medium and heavy categories in their teens. The type of research used is descriptive. The sample in this study were 41 active smokers with inclusion criteria, namely active smokers, adolescents less than 18 years of age, male sex, not taking drugs, and had fasted 8-12 hours. The sampling technique used is random. The samples were then examined for cholesterol using the CHOD-PAP method. From the results of the study, 26 (63.4%) respondents had normal cholesterol levels, 10 (24.4%) respondents experienced total cholesterol levels in the threshold category, and 5 (12.2%) respondents experienced total cholesterol levels in the high category. From these results, it can be concluded that most of the active smokers in the Cilawu District have cholesterol levels (<200 mg/dL) with an average value of 157 mg/dL. With this research, it is hoped that adolescent smokers can reduce the number of cigarettes consumed, which can stop smoking.